Report on Workshop "Marine Science Program using a Charter Research Vessel" -Report of activities in JARE-43 and science plan for JARE-44- - Tsuneo Odate; Mitsuo Fukuchi (National Institute of Polar Research, 2002)
A workshop on "Marine Science Program using a Charter Research Vessel" was held on 19th and 20th June 2002 at the National Institute of Polar Research (NIPR), Tokyo, with 30 participants. On the first day, scientific activities during the cruise of RV Tangaroa, chartered by the 43rd Japanese Antarctic Research Expedition (JARE), were reported. These activities will be reported at the symposium of the Oceanographic Society of Japan in October 2002. Further detail results will be discussed at the 25th Symposium on Polar Biology at NIPR in December 2002. On the second day, science plans for JARE-44, which will charter a research vessel again, were discussed. During 2002/2003 season, the "Aurora Australis", Australian National Antarctic Research Expedition, and the "Umitaka Maru", Tokyo University of Fisheries, plan research cruises in the same sea area as the JARE charter ship, in October - November 2002 and January - February 2003, respectively. "Shirase" will pass through the area in March 2003. Consequently, time serial observations will be possible using these vessels. Detail observations to reveal the relationship between biological processes and global climate change will be conducted along 140oE south of 65oS, where two different ecological structures were observed during the cruise of JARE-43. In addition to these observations, formation of the Antarctic bottom water will be studied.